Le « Plan de Rome » de Paul Bigot à l’Université de Caen et son double virtuel : de l’objet patrimonial à l’outil scientifique - Sophie Madeleine; Philippe Fleury (In Situ)
Work on developing a virtual model of the city of Rome in the fourth century A.D. began in Caen in 1994. The project is based on a 70-square meter model of ancient Rome that was made by the architect P. Bigot at the beginning of the 20th century, known in French as the “Plan de Rome”. The Plan de Rome is an exceptional piece of our cultural heritage whose only equivalents are its twin which is in Brussels and the model made by I. Gismondi which is in the Museum of Roman Civilization in Rome. The work involves the development of a fully interactive model of ancient Rome that includes both its architecture and the machinery in use. In reconstituting the past, scholars are able to test their assumptions from the architectural and topographic viewpoints and test machine functionality. The visitor to the virtual site is able to wander through a full-scale city and enter most of its large public monuments and a few residences The work preliminary to the reconstruction itself involves the analysis of ancient source materials, which is currently being performed by the project team’s members who have recourse to outside experts for help with specific points. The body of source material is directly accessible via the interactive model.